Crying for repression: populist and democratic biopolitics in times of COVID-19 - Schubert, Karsten (2020)
Abstract: We live in very Foucauldian times, as the many think-pieces published on biopolitics and COVID-19 show. Yet what is remarkable - biopolitically - about the current situation has gone largely unnoticed: We are witnessing a new form of biopolitics today that could be termed populist biopolitics. Awareness of this populist biopolitics helps illuminate what is needed today: democratic biopolitics